Straight-line and change-of-direction intermittent running in professional soccer players - Fessi, M. S.; Farhat, F.; Dellal, A.; Malone, J. J.; Moalla, W. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To investigate the difference between straight-line (STL) and change-of-direction (COD) intermittent-running exercises in soccer players. Methods: Seventeen male professional soccer players performed the agility T test and 6 intermittent-running exercises: 10 s at 130% of maximal aerobic speed (MAS) alternated with 10 s of rest (10-10), 15 s at 120% of MAS alternated with 15 s of rest (15-15), and 30 s at 110% of MAS alternated with 30 s of rest (30-30) both in STL and with COD. All exercises were monitored using a global positioning system. Heart rate was measured during exercises, and rating of perceived exertion (RPE) was collected postexercise. The difference (Delta) between covered distance in STL and COD exercises at a similar load was calculated, and relationships between T test and Delta distance were analyzed. Results: COD intermittent exercises showed a significantly decreased distance covered and an increase in the number of accelerations, peak heart rate, and RPE compared with STL intermittent exercises at a similar load. High relationships were observed between T-test performance and Delta distance in 10-10 (r=.72, P<.01) and 15-15 (r=.77, P<.01), whereas no significant relationships were observed between T-test performance and Delta distance in 30-30 (r=-.37, P=.2). Conclusion: Intermittent COD exercises were associated with higher acceleration, peak heart rate, and RPE than STL during 10-10 and 15-15 exercises. The ability to rapidly change direction is crucial to perform intense sport-specific running in professional soccer players.